(3CSGSjGJ JShjb GdNOeGJs - (3eSGdJI(B, (3SajGfs; (3YUeGfj, SajGfs ((3GdLRGFQs (3OGQ GdHGMK ddfTQ hGdETgGQs, 2023)
(3eONd eaGgjej Mhd GdNOeI, NUGFU GdNOeGJ h GdfJGFL GdeJQJHI YdjgG, cPdc JUfja GdNOeGJ hWHjYJgG, eY bQGQGJ GdeRjL GdJShjbj RgQI GdNOeGJ, hCNjQG GdJMdjdGJ GdeQJHWI HGdYQV GdNOej(B.s
Keywords: (3GdJShjbs; (3JShjb GdNOeGJs